An Analysis of the Causes of Multivalence in Hafez’s Discourse: A Hermeneutic Approach - Saghe’i, Saeed; Khadivar, Hadi (Richtmann Publishing, 2012)
From the viewpoint of hermeneutics, texts are divided into open and closed texts. In contrast to closed texts, which areinflexibly structured, open texts are those which, according to Eco, are intended to lead to plural interpretations; these texts allow greatfreedom to the readers in the interpretation process and are preferred by intellectual people, since they, as opposed to common people,do not seek immediate pleasure from the text but try to go deep into the text and appreciate the miraculous power of such texts. Thepresent paper is an attempt to show that Hafez’s poems belong to open texts. Moreover, case studies on his poems, by means of ahermeneutic approach as well as the ideas of Eco and Bakhtin, will demonstrate that multivalence in Hafez’s poems stems from generalliterary and linguistic factors, his own personality, and sometimes from issues related to the readers. The results of the paper areillustrated at the end of a paper through a tree diagram.